Immobilization of cellulase on carbon nanotubes for cellulosic materials hydrolysis - Abd, Rasha Mohammed (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
The fast growing oil palm industry in Malaysia generates, amongst other wastes, empty fruit bunches (EFB) which consist of cellulosic materials. It is one of the major sources of greenhouse gases (GHG). The bioconversion of cellulosic materials in oil palm empty fruit bunches (OPEFB) to valuable products will be the solution to the disposal problem and hence minimize the pollution. The degradation of cellulosic materials to glucose can be achieved using cellulase enzyme as it can work with high catalysis under mild condition. However, cellulase enzyme does not fulfill the industry requirement because it is unstable, soluble, and undergo inhibitions. In this study, cellulase was immobilized on functionalized multi wall carbon nanotubes (MWCNTs) in a solution of N-hydroxysuccinimide (NHS) and 1-ethyl-3-(3- dimethylamino propyl) -carbodiimide hydrochloride (EDAC). The results from fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM), and BET analysis of functionalized multi wall carbon nanotubes (MWCNTs) showed that the acid treatment helps in imparting hydroxyl, carboxyl, and carbonyl groups. The preliminary screening using Plackett–Burman design (PBD) showed that only three parameters (EDAC dose, pH, and temperature) have significance effects on immobilization. The optimization using face centered central composite design (FCCCD) showed that the optimum conditions to immobilize cellulase enzyme is at pH 4.5, 30 °C temperature, and 1 ml of (10 mg/ml) EDAC stock solution. The amount of cellulase enzyme immobilized on MWCNTs was about 98% at the optimum conditions as an optimum value. The existence of cellulase enzyme on MWCNTs was confirmed by FESEM and FTIR techniques. Moreover, degradation of OPEFB using immobilized enzyme resulted in high reducing sugar concentration of 0.62 g/g at the end of 48 hrs of the hydrolysis period. The results of the present study are in agreement with that of commercial cellulase enzyme which supports our finding.